مستوى جودة التعليم العالي من وجهة نظر طلبة جامعة يحي فارس المدية (الجزائر). - boulasnam, mouhamed (Finance and Business Economies Review, 2018)
Yahia Fares University student’s. A questionnaire has been designed to answer the study problem. The first part introduces the descriptive information of students, while the second part emphasizes the quality of the higher education. The study sample includes 379 students from the whole society of 22343 students during 2016-2017. The study concluded that the student’s evaluation of higher education quality has a medium level exept the education evaluation task which was less the average level. Many factors explain the insufficient level of the higher education quality from the viewpoint of Yahya Fares University such as the wikness of the education evaluation task. The researchers suggested the application of electronic questionnaire that will be linked to the Universities’s Websites